2008
DOI: 10.1086/588195
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to Mumps Vaccine in Adults Who Were Vaccinated in Childhood

Abstract: T and B cell immunity to mumps was detected in adults at least 10 years after immunization. Except for IFN-gamma release, responses in vaccinated adults paralleled those observed in naturally immune individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 36 publications
(40 reference statements)
4
40
1
1
Order By: Relevance
“…Similar findings were reported by Jokinen et al, who found mumps antigen-speciˆc lymphoproliferative response in 100z of subjects that naturally acquired immunity to the mumps virus (16). In research performed by Hanna-Wakim et al, 80z of naturally immune individuals had a positive stimulation index (15). Cell-mediated immunity to mumps in vaccinated individuals was lower than that in naturally immune adults (15,16).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar findings were reported by Jokinen et al, who found mumps antigen-speciˆc lymphoproliferative response in 100z of subjects that naturally acquired immunity to the mumps virus (16). In research performed by Hanna-Wakim et al, 80z of naturally immune individuals had a positive stimulation index (15). Cell-mediated immunity to mumps in vaccinated individuals was lower than that in naturally immune adults (15,16).…”
Section: Discussionsupporting
confidence: 82%
“…In research performed by Hanna-Wakim et al, 80z of naturally immune individuals had a positive stimulation index (15). Cell-mediated immunity to mumps in vaccinated individuals was lower than that in naturally immune adults (15,16). There was a significant correlation between frequency of CTLs and proliferation of CD8+ T lymphocytes.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This suggested that certain population groups might be incompletely vaccinated, and that the humoral immunity provided by vaccination gradually declined over time. The seropositivity rate increased again after 20 years of age, probably as a consequence of natural infection from greater exposure to the surrounding community [13].…”
Section: Discussionmentioning
confidence: 97%